2008
DOI: 10.1016/j.immuni.2008.04.002
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 Suppresses Activation-Induced Cytidine Deaminase-Mediated Myc-Igh Translocation

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that regulate vast networks of genes that share miRNA target sequences. To examine the physiologic effects of an individual miRNA-mRNA interaction in vivo, we generated mice that carry a mutation in the putative microRNA-155 (miR-155) binding site in the 3'-untranslated region of activation-induced cytidine deaminase (AID), designated Aicda(155) mice. AID is required for immunoglobulin gene diversification in B lymphocytes, but it also promotes chromosomal translocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
360
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(386 citation statements)
references
References 73 publications
24
360
1
1
Order By: Relevance
“…Indeed, it is possible that the diminished CSR obtained with some of the export-proficient mutant NESs might at least in part be the direct result of their diminished stability: the abundance of AID in normal B cells is known to be tightly controlled, with the efficiency of CSR being very sensitive to AID expression levels (15)(16)(17)(18)(19). Such a requirement for both export and abundance might nicely explain the CSR-deficiency exhibited by the AID P20 mutant (8), which carries a 34-aa insertion upstream of the NES, as we find that this mutant exhibits diminished stability although retaining a functional export sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is possible that the diminished CSR obtained with some of the export-proficient mutant NESs might at least in part be the direct result of their diminished stability: the abundance of AID in normal B cells is known to be tightly controlled, with the efficiency of CSR being very sensitive to AID expression levels (15)(16)(17)(18)(19). Such a requirement for both export and abundance might nicely explain the CSR-deficiency exhibited by the AID P20 mutant (8), which carries a 34-aa insertion upstream of the NES, as we find that this mutant exhibits diminished stability although retaining a functional export sequence.…”
Section: Discussionmentioning
confidence: 99%
“…41 It has also been demonstrated that the failure of miR-155-deficient B cells to generate highaffinity switched antibodies appears not because of a defect in somatic hypermutation or class-switch recombination, but more likely to a defect in the differentiation or survival of plasmablasts. 42 The predominance of infra-expressed miRNAs in myeloma samples is consistent with the global decrease in miRNA levels observed in other human cancers.…”
Section: Tablementioning
confidence: 99%
“…This is highlighted by the cancer predisposition phenotype observed in transgenic mice overexpressing AID 7 , by the finding that ectopic SHM can occur in proto-oncogenes and tumor suppressor genes [8][9][10] and by the involvement of AID in oncogenic chromosomal translocations 11,12 . AID is normally induced in germinal center B cells 13 but in order to ensure that the genetic modifications it can cause are largely restricted to the Ig loci, there are multiple points of posttranscriptional regulation such as regulation of mRNA stability and translation [14][15][16] , subcellular localization 17,18 , protein stability 19 and modification by phosphorylation [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%